2005
DOI: 10.1590/s0004-282x2005000500010
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in the elderly: clinical, electrophysiological, therapeutic and outcome features

Abstract: -There are few papers devoted to geriatric Guillain-Barré (GBS) and many related issues re m a i n u n a n s w e re d . Objective: To describe clinical, electrophysiological and therapeutic features in this age. Method: Clinico-epidemiological data and therapy of GBS patients older than 60 years were reviewed. Hughes scores were used to quantify neurological deficit and define outcome. Results: Among 18 patients (mean age 64.8 years), 9 had evident pro d rome and 80% noticed initially sensory-motor deficit. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…20 Nine other studies (four prospective, five retrospective) concluded that TPE and IVIg were both viable options or that TPE was slightly more efficacious than IVIg for GBS treatment (LoE: 2-4). [22][23][24][25][26][27][28][29][30] Similar to the clinical trials above, most of these studies agreed that the safety of TPE and IVIg was acceptable. One study indicated that TPE may be more frequently associated with complications.…”
Section: Efficacy Of Ivig and Tpe Therapies Per Categorymentioning
confidence: 59%
See 1 more Smart Citation
“…20 Nine other studies (four prospective, five retrospective) concluded that TPE and IVIg were both viable options or that TPE was slightly more efficacious than IVIg for GBS treatment (LoE: 2-4). [22][23][24][25][26][27][28][29][30] Similar to the clinical trials above, most of these studies agreed that the safety of TPE and IVIg was acceptable. One study indicated that TPE may be more frequently associated with complications.…”
Section: Efficacy Of Ivig and Tpe Therapies Per Categorymentioning
confidence: 59%
“…One study indicated that TPE may be more frequently associated with complications. 23 Of note, the route of TPE administration (central versus peripheral), the TPE device and the IVIg producer were often insufficiently detailed. Ravasio et al 22 reported having used IVIg from six different producers in their study, but did not state which product was used in which patients.…”
Section: Resultsmentioning
confidence: 99%
“…Geniş hasta serileri, popülasyon çalışmaları ve geniş kapsamlı kontrollü çalışmalar aşağıdakilerin prognoz açısından olumsuz faktörler olduğunu tutarlı bir şekilde ortaya koymuştur: ileri yaş, geçirilmiş gastrointestinal enfeksiyon, Campylobacter enfeksiyonu için serolojik kanıtlar ya da gaita kültürü kanıtları, ağır akut hastalık (yapay solunum gereksinimi ya da üst ekstremitelerde ileri derecede güçsüzlük), akson dejenerasyonuna ilişkin elektrofizyolojik kayıtlar ve plazma değişimi ya da intravenöz immünglobulin tedavisinin yapılmamış olması GBS' deki olumsuz prognostik faktörlerdir [7][8][9][10][11][12][13]. İleri yaş grubunda hastalar daha kötü belirtilerle gelmekte ve hastalık daha ağır seyretmektedir [1,14].…”
Section: Discussionunclassified
“…De acordo com os estudos de FrançaJunior (2005) o desenvolvimento de paralisia flácida aguda, provocado pela doença, e que gera grave incapacidade é mais frequente em idosos, tendo este público pior prognostico para a doença. Sendo necessários maiores estudos para o entendimento e manejo da Síndrome de Guillain Barré no idoso.Residência Multiprofissional Em Cuidados Continuados Integrados: Demandas De Homens Idosos Apresentadas Ao Serviço Social 60…”
unclassified